Comparative evaluation of safety parameters at the preclinical and clinical stages of the study of the Reamberin® (LLC "POLYSAN") - V. B. Vasilyuk; M. V. Faraponova; G. I. Syraeva; A. B. Verveda; A. V. Belskaya; A. V. Shults; L. G. Kubarskaya; E. A. Zolotoverkhaya (LLC "Publisher OKI", 2022)
Relevance. Interpretation of the preclinical trials data is fundamental importance. The correctness of extrapolation of data obtained from animals to humans is due to the qualitative and quantitative diversity of the systems tested the recorded parameters and approaches to their interpretation, as well as statistical methods in determining the possible risk to humans. Aim. Comparative assessment of the safety and tolerability parameters obtained during the preclinical and clinical trials of the Reamberin® (LLC «POLYSAN») and the development of approaches to improving clinical trial planning processes for assessing safety and tolerability, taking into accounts the results of preclinical studies. Materials and methods. A comparative analysis of the safety parameters that arose during a clinical study involving healthy volunteers and deviations from the control levels of clinical and laboratory parameters established at the stage of a preclinical study on outbred rats and rabbits of the chinchilla breed of a drug with an international non-proprietary name (INN): meglumine sodium succinate (trade name (TN) Reamberin® (LLC «POLYSAN»)). Results. Unidirectional deviations from normal (control) values were established. Isolated cases of adverse events among healthy volunteers (increased activity of hepatic transaminases, changes in blood pressure) were identified. This facts didn't correlate with the preclinical study. The number of comparable indicators in laboratory animals, for which statistically significant differences were established between the experimental and control groups, significantly exceeded the number of signs in the form of adverse events among healthy volunteers.